PUBLIC-PRIVATE PARTNERSHIP IN VOCATIONAL EDUCATION: CHALLENGES AND OPPORTUNITIES (Innovative professional education, 2024)
Public-private partnerships (PPPs) in education: potentials and risks. The complexity of PPPs in education and their impact on accessibility, quality, and social justice are reflected upon. Various aspects of the influence of public-private partnerships in education are considered, emphasizing the necessity of careful regulation of PPPs to ensure the effectiveness and development of education.
Keywords: public-private partnerships, education, globalization, social justice, accessibility, quality of education